Evaluation of Global Genomic DNA Methylation in Human Whole Blood by Capillary Electrophoresis UV Detection. (3rd December 2017) - Zinellu, Angelo; Sotgiu, Elisabetta; Assaretti, Stefano; Sotgia, Salvatore; Paliogiannis, Panagiotis; Pintus, Gianfranco; Mangoni, Arduino A.; Carru, Ciriaco
Abstract : Alterations in global DNA methylation are implicated in various pathophysiological processes. The development of simple and quick, yet robust, methods to assess DNA methylation is required to facilitate its measurement and interpretation in clinical practice. We describe a highly sensitive and reproducible capillary electrophoresis method with UV detection for the separation and detection of cytosine and methylcytosine, after formic acid hydrolysis of DNA extracted from human whole blood. Hydrolysed samples were dried and resuspended with water and directly injected into the capillary without sample derivatization procedures. The use of a run buffer containing 50 mmol/L BIS-TRIS propane (BTP) phosphate buffer at pH 3.25 and 60 mmol/L sodium acetate buffer at pH 3.60 (4 : 1, v/v ) allowed full analyte identification within 11 min. Precision tests indicated an elevated reproducibility with an interassay CV of 1.98% when starting from 2 μg of the extracted DNA. The method was successfully tested by measuring the DNA methylation degree both in healthy volunteers and in reference calf thymus DNA.